LIABILITY IN THE FIELD OF LICENSING OF PHARMACEUTICAL ACTIVITIES (European Journal of Interdisciplinary Research and Development, 2023)
The purpose of this study is to compare the normative legal acts regulating the issues of administrative and criminal liability for the illegal implementation of pharmaceutical activities in the Republic of Uzbekistan.